2016
DOI: 10.1039/c5re00080g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of the liquid organic hydrogen carrier compound dibenzyltoluene – reaction pathway determination by 1H NMR spectroscopy

Abstract: The catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) was investigated by 1 H NMR spectroscopy in order to elucidate the reaction pathway of its charging process with hydrogen in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 21 publications
5
79
0
1
Order By: Relevance
“…By appropriate measures,n early full degree of hydrogenationi sr eached (e.g.,r eactor design, liquid recycling). [25,27] Thes till-warm product, H18-DBT, is stored in atank. Thedehydrogenation reactor and the fuel cell form the dehydrogenation strand.H 18-DBT is pumped from its storage tank and is preheated again by recuperation with the product stream before entering the reactor.…”
Section: Storagesystem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…By appropriate measures,n early full degree of hydrogenationi sr eached (e.g.,r eactor design, liquid recycling). [25,27] Thes till-warm product, H18-DBT, is stored in atank. Thedehydrogenation reactor and the fuel cell form the dehydrogenation strand.H 18-DBT is pumped from its storage tank and is preheated again by recuperation with the product stream before entering the reactor.…”
Section: Storagesystem Descriptionmentioning
confidence: 99%
“…Heat management of the reactor consists of an electric heater for start up and a combination of recuperation of liquid in/out streams and a separate cooling cycle with a pumped heat‐transfer fluid (HTF) cooled by a fan to ensure constant temperature along the reactor tubes. By appropriate measures, nearly full degree of hydrogenation is reached (e.g., reactor design, liquid recycling) . The still‐warm product, H18‐DBT, is stored in a tank.…”
Section: Introductionmentioning
confidence: 99%
“…Do et al . showed in a recent publication that the hydrogenation of the closely related LOHC material dibenzyl toluene proceeds ring‐wise and with a clear side‐ring (SR) preference.…”
Section: Introductionmentioning
confidence: 99%
“…Do et al [20] showed in ar ecent publicationt hat the hydrogenation of the closely related LOHCm aterial dibenzyl toluene proceedsr ing-wise and with ac lear side-ring( SR)p reference. First, this means that the reactionp roduces mainly fully hydrogenated or dehydrogenated rings.S econd, it meanst hat the hydrogenation of the three rings in the molecule mainly proceeds in the sequence side-side-middle.…”
Section: Introductionmentioning
confidence: 99%
“…Although the extended ageing resulted in a larger BET surface area of Ru/ZrO 2 , the hydrogenation activity and Ru dispersion turned out to be in a volcano-shaped dependence on the ageing period. Ru, the cheapest among noble metals, was examined the most active for several LOHC materials including N-ethylcarbazole, [4] H 0 -MBT, [1,5] H 0 -DBT, [1,6] and 2-(n-methylbenzyl)pyridine. Consequently, the hydrogenation activity trend of the present Ru/ZrO 2 was a combined consequence of the surface OH content and surface area of zirconium hydroxide.…”
mentioning
confidence: 99%